Teaching chinese as an international language a Singapore perspective - Yeng-Seng, Goh (Cambridge, Unitedd Kingdom Cambridge University Press, 2017)
"Bilingual and bicultural scholar Yeng-Seng Goh offers the first in-depth English language analysis of global Chinese, exploring the spread of Chinese beyond China and its emergence as a global language. Approaching the topic from a Singapore perspective, Goh uses this fascinating language ecosystem, with its unique bilingual language policy, as a case study for Chinese language learning. Offering clear insights into the pedagogy of teaching Chinese as an international language (TCIL), this book covers a range of important topics, such as the use of English in the teaching of Chinese, the teaching of Chinese by non-native teachers, information and communications technology in L2 learning and teaching, and the progressive testing of receptive skills. In doing so, it presents a new, integrative approach to the compilation of Chinese learner's dictionaries, an innovative bilingual hybrid model for training TCIL teachers, and a solid theoretical framework for Masters of Arts programmes in TCIL"--Provided by publisher.
Keywords: Language planning -- Singapore; Language policy -- Singapore; Multilingualism -- Singapore; Chinese language -- Study and teaching -- Singapore